2017
DOI: 10.3892/ol.2017.6443
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of angiopoietin 2-small interfering RNA plasmid/chitosan magnetic nanoparticles in a mouse model of malignant melanoma in vivo

Abstract: The aim of the present study was to observe the in vivo targeting characteristic of angiopoietin 2-small interfering RNA (Ang2-siRNA) plasmid/chitosan magnetic nanoparticles in an established nude mouse model of malignant melanoma (MM) under an external magnetic field. The nude mouse MM model was first established, then divided into 3 groups, including the control group, the non-targeting group and the target group, the control group was given normal saline and the non-targeting and targeting groups were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…To address these limitations, chitosan magnetic nanoparticles (CMNPs) containing Ang-2 small interfering RNA (Ang2-siRNA) plasmids were developed, and these nanoparticles could lead to significant inhibition of angiogenesis in a malignant melanoma model. 19 Magnetic iron oxide nanoparticles are the core of Ang2-CMNPs. The Ang2-siRNA plasmid particles were encapsulated by chitosan, which does not increase systemic toxicity and is stable in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To address these limitations, chitosan magnetic nanoparticles (CMNPs) containing Ang-2 small interfering RNA (Ang2-siRNA) plasmids were developed, and these nanoparticles could lead to significant inhibition of angiogenesis in a malignant melanoma model. 19 Magnetic iron oxide nanoparticles are the core of Ang2-CMNPs. The Ang2-siRNA plasmid particles were encapsulated by chitosan, which does not increase systemic toxicity and is stable in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…28 Our previous study also showed that Ang2-CMNPs significantly inhibited the growth of malignant melanoma in vivo. 19 We further evaluated the underlying mechanism of Ang2-CMNP-mediated inhibition of tumor growth. Angiogenesis occurs throughout tumor development and metastasis, and Ang2 has been shown to be essential during the proangiogenic and aggressive phases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations